Akt phosphorylates myc-associated zinc finger protein (MAZ), releases P-MAZ from the p53 promoter, and activates p53 transcription. Issue 1 (28th May 2016) - Lee, Wei-Ping; Lan, Keng-Hsin; Li, Chung-Pin; Chao, Yee; Lin, Han-Chieh; Lee, Shou-Dong
Highlights: p53 is stabilized through Akt/Arf-mediated Mdm2 inhibition upon oncogene activation. Myc-associated zinc finger protein (MAZ) is a transcriptional repressor of the p53 promoter. Akt phosphorylates MAZ at Thr385. P-MAZ detaches from the p53 promoter, leading to de-repression of p53 transcription. Abstract: The p53 protein is a cell cycle regulator. When the cell cycle progresses, p53 plays an important role in putting a brake on the G1 phase to prevent unwanted errors during cell division. Akt is a downstream kinase of receptor tyrosine kinase. Upon activation, Akt phorphorylates IKK that then phosphorylates IκB and releases NF-κB, leading to transcriptional activation of Dmp1. Dmp1 is a transcriptional activator of Arf. It has been known that oncogene activation stabilizes p53 through transcriptional activation of Arf, which then binds and inhibits Mdm2. In the current study, we show that myc-associated zinc finger protein (MAZ) is a transcriptional repressor of the p53 promoter. Akt phosphorylates MAZ at Thr385, and the phosphorylated MAZ is released from the p53 promoter, leading to transcriptional activation of p53, a new mechanism that contributes to increased p53 protein pool during oncogene activation.